2005
DOI: 10.1038/sj.bjc.6602516
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin-induced activation of the death receptor-mediated apoptosis pathway circumvents acquired doxorubicin resistance in SCLC cells

Abstract: Small-cell lung cancers (SCLCs) initially respond to chemotherapy but are often resistant at recurrence. A potentially new method to overcome resistance is to combine classical chemotherapeutic drugs with apoptosis induction via tumour necrosis factor (TNF) death receptor family members such as Fas. The doxorubicin-resistant human SCLC cell line GLC 4 -Adr and its parental doxorubicinsensitive line GLC 4 were used to analyse the potential of the Fas-mediated apoptotic pathway and the mitochondrial apoptotic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
4
21
0
Order By: Relevance
“…We previously reported that exposure of the MRP1-overexpressing doxorubicin-resistant SCLC cell line GLC 4 -Adr to indomethacin resulted in caspase-8-and caspase-9-dependent apoptosis induction, suggesting the involvement of the extrinsic and intrinsic apoptosis pathways. In contrast, exposure of the parental cell line GLC 4 to indomethacin did not induce apoptosis (De Groot et al, 2005). Indomethacin as well as MK571 increase doxorubicin sensitivity in these GLC 4 cell lines.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…We previously reported that exposure of the MRP1-overexpressing doxorubicin-resistant SCLC cell line GLC 4 -Adr to indomethacin resulted in caspase-8-and caspase-9-dependent apoptosis induction, suggesting the involvement of the extrinsic and intrinsic apoptosis pathways. In contrast, exposure of the parental cell line GLC 4 to indomethacin did not induce apoptosis (De Groot et al, 2005). Indomethacin as well as MK571 increase doxorubicin sensitivity in these GLC 4 cell lines.…”
mentioning
confidence: 83%
“…Compared with the parental cell line GLC 4 , the doxorubicinresistant sub-line GLC 4 -Adr strongly overexpresses MRP1 and is highly sensitive to indomethacin (De Groot et al, 2005). The role of MRP1 in indomethacin sensitivity was investigated using an MRP1 siRNA approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fas membrane expression was determined in GIST cells by flow cytometry as described previously (De Groot et al, 2005). Phycoerythrin (PE)-conjugated mouse anti-Fas monoclonal antibody (clone DX-2, 1 : 10; BD Pharmingen, Alphen aan de Rijn, The Netherlands) was used.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Western blotting was performed as described previously (De Groot et al, 2005). Primary antibodies were goat anti-Fas (polyclonal, 1 : 400; Santa Cruz, Heerhugowaard, The Netherlands), mouse anti-FasL and mouse anti-caspase 3 (clone 33 and clone 19, respectively, 1 : 1000; BD Transduction Laboratories, Alphen aan den Rijn, The Netherlands), rabbit anti-cleaved caspase 3 and rabbit anti-caspase 6 (1 : 1000; Cell Signalling Technology, Bioké, Leiden, The Netherlands), mouse anti-caspase 8 (clone 1C12, 1 : 500; Cell Signalling), and mouse anti-actin (clone C4, 1 : 20 000; ICN Biomedicals, Zoetermeer, The Netherlands).…”
Section: Western Blot Analysismentioning
confidence: 99%